Establishing a relationship between industry and academia: challenges, lessons learned and benefits - Tiengo, Willy; Fonseca, Baldoíno; Paes, Elysanne; Paes, Rodrigo; Vieira, Tiago; Ribeiro, Márcio; Peixoto, Rodrigo; Bibiano, Davi (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
Several benefits are expected from the establishment of the relationship between academia and industry. For example, we can mention the identification and solution of real problems, greater availability of financial resources, innovation and qualified training of human resources. However, establishing this relationship is not an easy task, especially for university researchers where there is still no history of relations with industry. Several challenges may arise, whether in prospecting and contracting projects with the industry, or even in the execution of projects. This article presents an account of the experience of researchers at the Federal University of Alagoas (UFAL) in prospecting, contracting and executing software and hardware projects with Brazilian companies over five years. In particular, it reports the main challenges faced, the lessons learned and the benefits obtained for UFAL and the companies.